Effectiveness of Dormancy-Breaking Treatments on the Germination of Indigofera zollingeriana - Burhan Efendi; Zaki Ismail Fahmi; Muhammad Nidhomun Ni’am; Zainudin Al Wahid; Mawakia Anwar (Universitas Muhammadiyah Palembang, 2025)
The availability of high-quality forage remains a major challenge in ruminant livestock systems, particularly during the dry season. Indigofera zollingeriana is a promising leguminous species with high protein content, yet its cultivation is constrained by high seed dormancy. This study aimed to evaluate the effectiveness of various dormancy-breaking treatments on the germination of I. zollingeriana seeds, both in general (across treatment groups) and specifically (to determine the most effective treatment). The experiment was arranged in a completely randomized design (CRD) with 17 non-factorial treatments and three replications, using two germination test methods: Top of Paper (TOP) and Between Paper (BP). Data were analyzed using ANOVA and orthogonal contrast tests at 5% and 1% significance levels. Results showed that all treatments (K1–K16) significantly increased germination percentage compared to the control, with averages of 49.88% vs. 36.00% (TOP) and 53.69% vs. 41.00% (BP). The most effective treatment was immersion in 95% sulfuric acid (H₂SO₄) for 10 minutes, which achieved the highest germination rate (88%) and the lowest dormancy intensity (0%), significantly outperforming physical, biological, and hormonal treatments. These findings indicate that short-duration chemical scarification can serve as a standard treatment for large-scale I. zollingeriana seed production. Further studies are needed to evaluate the physiological safety of the treatment and its impact on early seedling growth in field conditions.